PROCESSING OF RESULTS FROM A THERMAL FEM ANALYSIS USING THE LOCK-IN METHOD AND COMPARISON WITH EXPERIMENT - Ondrej ŠTALMACH; Vladimír DEKÝŠ; Pavol NOVÁK; Milan SAPIETA (Scientific Journal of Silesian University of Technology. Series Transport)
This article dealt with the comparison of results obtained from an experiment and from the numerical thermal FEM analysis. Sample with defects were printed on a 3D printer. A thermal wave from the halogen lamp to excite the front surface of the sample was used in the next step and the response was measured by a thermal camera. After processing the data in the software DisplayIMG, a phase image was created representing the 2D image of the material at a certain depth under the surface of the model. Lock-in method was applied to the results from the numerical thermal FEM analysis and the phase image was created. The programs code were created in MATLAB for a 4 points, multiple points and differential lockin method which were compared with the results from the experiment.